Data styling in web mapping applications with a focus on environmental health. Issue 4 (2nd October 2017) - Harciníková, Tatiana; Benová, Alexandra; Feciskanin, Richard; Chudý, Radoslav; Kožuch, Miroslav; Pelech, Vladimír; Schmidt, Tomáš; Stanková, Hana; Vališ, Juraj; Mičietová, Eva
Abstract: Interpretation of data visualized in maps strongly depends on the experience of map reader and on the way the data are presented. Styling the data is crucial especially when creating maps for users with weaker cartographic knowledge and map reading experience. Because web mapping applications make spatial data more accessible to general public, this issue requires special attention in terms of their design. Here we present a styling approach for designing a web mapping application that assembles huge amount of data related to the issue of environmental health, based on our own experience with creating a web mapping application available athttps://uvp.geonika.sk/map/ (Department of Cartography … 2016). As the field of environmental health is multidisciplinary, it requires combination of data from various sources and of various types, topics and resolutions. Various data were compiled, requiring thoughtful approach to styling with regard to the users of the mapping application, who are supposed to be not only professionals (from the field of geography and geoinformatics as well as of medicine, epidemiology, environmental sciences etc.), but also general public. Many of such users do not possess adequate cartographic knowledge, which is the reason why the data styling had to reflect this limitation.